Full-Fledged VS Islamic Bank Windows: Which One Do Muslim Consumers Know Better and Prefer More? - Ratnasari, Nissa Ghulma; Hati, Sri Rahayu Hijrah; Chalid, Dony Abdul (Ekonomi Syariah IAIN Kudus, 2021)
The study aims to compare the knowledge of and preference for the Islamic banking window and the full-fledged Islamic bank among Muslim customers. Data were collected from 1171 banking clients. Data were analyzed using descriptive analysis. The results show most Muslim customers do not know the difference between the full-fledged Islamic bank and the Islamic banking window. Yet, most Muslim customers favor the full-fledged Islamic bank to the Islamic windows since it is perceived to be more sharia compliant. Thus, the study theoretically contributes to Muslim banking behavior literature by providing empirical evidence on customer knowledge and preference in choosing an Islamic bank. Besides, the study provides knowledge to both the Islamic bank windows and full-fledged Islamic bank on the Muslim customers' understanding of both channels' availability.